The great ideas of philosophy - Robinson, Daniel N. 1937-; Teaching Company (Chantilly, VA Teaching Co., 2005)
Presents sixty lectures by Professor Robinson, tracing the origins of philosophy and its history across the centuries.
From the Upanishads to Homer -- Philosophy, did the Greeks invent it -- Pythagoras and the divinity of number -- What is there? -- The Greek tragedians on man's fate -- Herodotus and the lamp of history -- Socrates on the examined life -- Plato's search for truth -- Can virtue be taught? -- Plato's Republic, man writ large -- Hippocrates and the science of life -- Aristotle on the knowable -- Aristotle on friendship -- Aristotle on the perfect life -- Rome, the Stoics, and the rule of law -- The Stoic bridge to Christianity -- Roman law, making a city of the once-wide world -- The light within, Augustine on human nature -- Islam -- Secular knowledge, the idea of university -- The reappearance of experimental science -- Scholasticism and the theory of natural law -- The Renaissance, was there one? -- Let us burn the witches to save them -- Francis Bacon and the authority of experience -- Descartes and the authority of reason -- Newton, the saint of science -- Hobbes and the social machine -- Locke's Newtonian science of the mind -- No matter? The challenge of materialism -- Hume and the pursuit of happiness -- Thomas Reid and the Scottish school -- France and the philosophes -- The federalist papers and the great experiment -- What is enlightenment? Kant on freedom -- Moral science and the natural world -- Phrenology, a science of the mind -- The idea of freedom -- The Hegelians and history -- The aesthetic movement, genius -- Nietzsche at the twilight -- The liberal tradition, J.S. Mill -- Darwin and nature's "purposes" -- Marxism, dead but not forgotten -- The Freudian world -- The radical William James -- William James' pragmatism -- Wittgenstein and the discursive turn -- Alan Turing in the forest of wisdom -- Four theories of the good life -- Ontology, what there "really" is -- Philosophy of science, the last word? -- Philosophy of psychology and related confusions -- Philosophy of mind, if there is one -- What makes a problem "moral" -- Medicine and the value of life -- On the nature of law -- Justice and just wars -- Aesthetics, beauty without observers -- God, really?
In five containers (26 cm.), with study guides (22 cm.) including lecture notes, outlines, timelines, glossaries, and bibliographical references.
Compact disc.
Daniel N. Robinson, Oxford University, lecturer.
Keywords: Philosophy -- History